Food and cultural studies - Ashley, Bob, 1946- (Studies in consumption and markets., 2004)
"Food and Cultural Studies re-examines the interdisciplinary history of food studies, from the semiotics of Barthes and the anthropology of Levi-Strauss to Elias's historical analysis and Bourdieu's work on the relationship between food, consumption and cultural identity. The authors then go on to explore subjects as divserse as food and nation, the gendering of eating in, the phenomenon of TV chefs, food-related moral panics and the ethics of vegetarianism."